FRI0497 The Interleukin-1 Inhibitor Canakinumab for Familial Mediterranean Fever: Long-Term Beneficial Effect in A Cohort of 14 Patients. (15th July 2016) - Laskari, K.; Boura, P.; Dalekos, G.N.; Garyfallos, A.; Karokis, D.; Pikazis, D.; Settas, L.; Skarantavos, G.; Tsitsami, E.; Sfikakis, P.P.
Abstract : Background: Interleukin-1 (IL-1) is a major mediator of the inflammatory cascade in Familial Mediterranean Fever (FMF) and an established therapeutic target (1). Objectives: To assess the efficacy and safety of the IL-1 inhibitor Canakinumab in adult and adolescent patients with refractory FMF. Methods: Fourteen patients (7 men) with genetically confirmed FMF, fulfilling the Tel Hashomer criteria, aged 38.5 years (median, range 13–70), with median disease duration of 14 years and active disease despite colchicine (n=9) or both colchicine and anakinra (n=5), received Canakinumab 150mg subcutaneously (sc) every 4 (n=7) or 6 (n=2) or 8 weeks (n=5) for a median of 18 months (range 7–53). Canakinumab was given as monotherapy in 8; 6 patients received concomitant treatment with colchicine and/or corticosteroids. Results: Eleven out of 14 patients (79%) achieved complete clinical remission (median time 2 months), while normalization of all laboratory parameters associated with inflammation occurred in 92% of patients (median time 3 months). The remaining patients achieved partial responses. Response was maintained until the last visit in all but 4 patients. Reducing the Canakimumab administration interval led to suppression of disease activity in three cases, whereas in another two patients drug administration intervals could be increased without disease exacerbation. The corticosteroid dose was significantly reduced during follow up. The FMF50 score (2) was achieved by 50% and 86% of patients at 1 and 12 months, respectively. Canakinumab was well tolerated; one patient experienced an urinary tract infection and another one a viral gastroenteritis. Conclusions: The rapid and sustained response to Canakinumab in the majority of our patients, together with the favorable safety profile, encourages its further use in FMF. References: Ter Haar N et al. Ann Rheum Dis. 2013;72(5):678–85. Ozen S et al. Ann Rheum Dis. 2014;73(5):897–901. Disclosure of Interest: None declared